Description of the marine nematode Hopperia australis sp. n. (Comesomatidae) from mangroves in Darwin, Australia, with a pictorial key to Hopperia species - Jensen, P. (Cah. Biol. Mar., 1992)
Locality: ; Cabinet:n125
Locality: ; Cabinet:n125; NeMys doc_id: 4192